2022
DOI: 10.1002/ehf2.14118
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure during the COVID‐19 pandemic: clinical, diagnostic, management, and organizational dilemmas

Abstract: The coronavirus 2019 (COVID-19) infection pandemic has affected the care of patients with heart failure (HF). Several consensus documents describe the appropriate diagnostic algorithm and treatment approach for patients with HF and associated COVID-19 infection. However, few questions about the mechanisms by which COVID can exacerbate HF in patients with high-risk (Stage B) or symptomatic HF (Stage C) remain unanswered. Therefore, the type of HF occurring during infection is poorly investigated. The diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 176 publications
(413 reference statements)
0
18
0
Order By: Relevance
“…The most prevalent cardiovascular phenotype in hospitalized patients with SARS-CoV-2 infections is acute decompensated heart failure, which is characterized by severe congestion, drastically altered hemodynamic state, and increased biomarkers of myocardial injury ( 61 ). Up to 25% of hospitalized patients with COVID-19 develop new cases of heart failure.…”
Section: Cardiovascular Manifestations Of Sars-cov-2 In Adultsmentioning
confidence: 99%
“…The most prevalent cardiovascular phenotype in hospitalized patients with SARS-CoV-2 infections is acute decompensated heart failure, which is characterized by severe congestion, drastically altered hemodynamic state, and increased biomarkers of myocardial injury ( 61 ). Up to 25% of hospitalized patients with COVID-19 develop new cases of heart failure.…”
Section: Cardiovascular Manifestations Of Sars-cov-2 In Adultsmentioning
confidence: 99%
“…These studies illustrate the close link between HF and VHD, with major geographical and age‐related differences. It should also be considered that delays in VHD interventions during the COVID‐19 pandemic may have aggravated HF in VHD patients, which was suggested from a systematic review of the relationships between HF and COVID‐19 pandemic with respect to epidemiology, pathogenetic mechanisms, and differential diagnoses 20 …”
Section: Valvular Heart Diseasementioning
confidence: 99%
“…It should also be considered that delays in VHD interventions during the COVID-19 pandemic may have aggravated HF in VHD patients, which was suggested from a systematic review of the relationships between HF and COVID-19 pandemic with respect to epidemiology, pathogenetic mechanisms, and differential diagnoses. 20 The haemodynamic consequences of AS, which exhibited the most pronounced increase over the age of 85 years in the KUNIUMI cohort, 19 may be decisive for a trajectory towards HF. Right and left heart catheterization in 477 patients undergoing aortic valve replacement (AVR) because of severe AS identified that the lowest mean arterial pressure quartile exhibited lower systemic vascular resistance and lower valvulo-arterial impedance, which may facilitate preserved stroke volume and filling pressures despite reduced left ventricular performance.…”
Section: Valvular Heart Diseasementioning
confidence: 99%
“…International societies have recently published reports focused on the management of patients with COVID-19 and HF based on the available data and personal experiences of physicians from the USA, Europe, and Asia [ 9 , 10 ]. Many gaps in knowledge remain to be clarified about the effective mechanisms involved in cardiac function deterioration during COVID-19 infection, the relationship between pre-existing HF diagnosis and outcome, and specific management for patients affected by HF to be applied in an acute setting or during convalescence periods [ 11 ].…”
Section: Introductionmentioning
confidence: 99%